38 Years Old Male Presenting with Male Infertility Found to Have Seminoma Testes: A Rare Case Report - Singla, Manoj (Edelweiss Applied Science and Technology, 2018)
38-year-old male present to the office with infertility and glucose permission, so for workup was negative on clinical examination found to have loss of right testicular sensation. Repeat blood work showed decreased FSH decreased TSH and decrease testosterone levels and I proceeded with obtaining testicular ultrasound that showed 2 discrete solid masses within the parenchyma of the right testicle both of which demonstrate internal blood flow. The larger lesion appears to contain calcification. The findings are most consistent with multifocal right testicular neoplasm. The left testicle is normal. He underwent radical inguinal orchidectomy and pathology showed stage IA T1 a seminoma the right testis after orchidectomy patient’s hormone level normalized and sperm count improved.